Strength estimation of a moving 125Iodine source during implantation in brachytherapy: application to linked sources - Tanaka, Kenichi (Oxford University Press, 2014)
This study sought to demonstrate the feasibility of estimating the source strength during implantation in brachytherapy. The requirement for measuring the strengths of the linked sources was investigated. The utilized sources were 125I with air kerma strengths of 8.38–8.63 U (μGy m2 h–1). Measurements were performed with a plastic scintillator (80 mm × 50 mm × 20 mm in thickness). For a source-to-source distance of 10.5 mm and at source speeds of up to 200 mm s–1, a counting time of 10 ms and a detector-to-needle distance of 5 mm were found to be the appropriate measurement conditions. The combined standard uncertainty (CSU) with the coverage factor of 1 (k = 1) was ∼15% when using a grid to decrease the interference by the neighboring sources. Without the grid, the CSU (k = 1) was ∼5%, and an 8% overestimation due to the neighboring sources was found to potentially cause additional uncertainty. In order to improve the accuracy in estimating source strength, it is recommended that the measurment conditions should be optimized by considering the tradeoff between the overestimation due to the neighboring sources and the intensity of the measured value, which influences the random error.